Muzâraah, SDGs, and the Welfare of Indonesian Farmers - Ali Aminulloh; Siti Zayyini Hurun In; Nano Suyatna; Udin Komarudin (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this article is to discuss a cooperative model of unproductive land use using a sharia-based cooperation system. This is done to improve the well-being of Indonesian farmers. This study employs the descriptive analysis method to examine a variety of relevant works of literature, journals, textbooks, and documents. Data analysis based on Miles and Huberman's theory. This research found that the use of unproductive lands is a divine command because God wants this earth to provide prosperity for humans. Agricultural products, which are the main products of land use, are the source of economic life for the majority of Indonesians. The agricultural sector also provides a large share of GDP and can survive in various conditions. However, agriculture has not been able to lift the dignity of farmers from poverty. As an agricultural country, Indonesia still has 12 million unproductive lands that can be optimized for use through sharia-based collaboration. With the help of capital, experts, and government support, it is possible to achieve the goals of the Sustainable Development Goals (SDGs), namely, no poverty and hunger by 2030, and a prosperous society.